2009
DOI: 10.1007/s11249-009-9526-3
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Lead Suspension in Oil Lubricant on the Sliding Wear Behaviour of Cast Iron

Abstract: This investigation pertains to the analysis of the sliding wear response of a cast iron over a range of applied pressures in the presence of an oil lubricant. The effect of varying concentrations of lead particles suspended in the oil lubricant on the wear behaviour of the cast iron was also examined. The wear rate increased with pressure initially at a lower rate followed by a higher rate of increase beyond a specific pressure. Furthermore, the presence of suspended lead particles up to a specific concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Further, the exposure and smearing of graphite and other solid lubricating phases on the wear surfaces ( Figure 12(c) and 13(b and d)) as well as flow of graphite in the sliding direction below the wear surface ( Figure 14, regions marked by B) suggest the lubrication effect produced by the solid lubricant particles dispersed in the oil and within the sample material to take part in controlling the wear behaviour. The solid lubricant film so formed and sticking debris on the wear surfaces reduce the extent of direct metal-to-metal contact and brings about improved wear response (Prasad, 2005(Prasad, , 2007b(Prasad, , 2009aPrasad et al, 2010bPrasad et al, , 20112010a, 2010cPrasad, 2010;Prasad (in press) ;Prasad, 2009b;Prasad and Modi, 2008). Plastic deformation on and below the wear surface ( Figure 12-14), sticking of debris on the wear surface ( Figure 13(a), region marked by A) and the presence of flakes in the debris (Figure 15, region marked by A) suggest adhesion to contribute to material loss.…”
Section: Wear Surfacesmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, the exposure and smearing of graphite and other solid lubricating phases on the wear surfaces ( Figure 12(c) and 13(b and d)) as well as flow of graphite in the sliding direction below the wear surface ( Figure 14, regions marked by B) suggest the lubrication effect produced by the solid lubricant particles dispersed in the oil and within the sample material to take part in controlling the wear behaviour. The solid lubricant film so formed and sticking debris on the wear surfaces reduce the extent of direct metal-to-metal contact and brings about improved wear response (Prasad, 2005(Prasad, , 2007b(Prasad, , 2009aPrasad et al, 2010bPrasad et al, , 20112010a, 2010cPrasad, 2010;Prasad (in press) ;Prasad, 2009b;Prasad and Modi, 2008). Plastic deformation on and below the wear surface ( Figure 12-14), sticking of debris on the wear surface ( Figure 13(a), region marked by A) and the presence of flakes in the debris (Figure 15, region marked by A) suggest adhesion to contribute to material loss.…”
Section: Wear Surfacesmentioning
confidence: 99%
“…Studies have shown that parameters like the content, nature, structure, mode of incorporation, etc. greatly influence the performance of solid lubricants (Boehringer, 1992;Bhushan and Gupta, 1991;Metals Handbook, 1992c;Kumar, 1994;Jha et al, 1986;Bhushan, 2001;Prasad, 2007a;Winer, 1967;Prasad, 2005Prasad, , 2007bPrasad, , 2009aPrasad et al, 2010bPrasad et al, , 2011Prasad et al, , 2010a. One of the ways to realize the benefit of solid lubricants is to suspend them in the base lubricant (oil) and direct the lubricant mixture at the sliding surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation